In Pursuit of Perspective: Does Vertical Perspective Disambiguate Depth from Motion Parallax?. (June 2013) - George, Jonathon M; Johnson, Joshua I; Nawrot, Mark
Motion parallax provides a dynamic, unambiguous, monocular visual depth cue. However, the lateral image motion in computer-generated motion parallax displays is depth-sign ambiguous. While mounting evidence indicates that the visual system uses an extra-retinal signal from the pursuit system to disambiguate depth, vertical perspective is a potential confound because it co-varies with the stimulus translation that produces the pursuit signal. Here the role of an extra-retinal pursuit signal and the role of vertical perspective in disambiguating depth from motion parallax were investigated. Through the careful isolation of each cue, the results indicate that observers have excellent depth discrimination with an extra-retinal pursuit cue alone, but have poor discrimination with vertical perspective alone. The conclusion is that vertical perspective does not play a role in the disambiguation of depth in small computer-generated motion parallax displays.